Faktor-Faktor yang Berhubungan dengan Status Imunisasi Lanjutan Pentavalen (DPT-HB-Hib) di Wilayah Kerja Puskesmas Labuhan Ratu Kota Bandar Lampung Tahun 2018 - Nanda Salsabila Itsa; Roro Rukmi Windi Perdani; Hanna Mutiara (MAJORITY, 2020)
The Pentavalent (DPT-HB-Hib) immunization is one of advanced immunization programmed by the goverment to prevent diseases such as diphteria, pertussis, tetanus, B-type hepatitis, and B-type Haemophilus influenzae. The lowest advanced pentavalent immunization coverage in Bandar Lampung is located at Labuhan Ratu Health Center (26,9%). Several factors are related to pentavalent immunization administration such as mother’s knowledge, mother’s attitude, mother’s job status, affordability of health services, and the role of health workers. Purpose of this research is to find out the factors related to advanced pentavalent immunization in the working area of Labuhan Ratu Public Health Bandar Lampung. This research used analytic observational method with cross-sectional approach. The sample of the research is 42 respondents in which live at work area of Labuhan Ratu Public Health Bandar Lampung city through purposive sampling method. The result of univariate analysis was 42,9% of respondents had complete advanced Pentavalent immunization status and the other 64,3% respondents had incomplete status. The result of bivariate analysis showed some variables had a correlation with advanced pentavalent immunization status such as mother’s knowledge (p-value 0,029), mother’s attitude (p-value 0,022) and mother’s job status (p value 0,014). Meanwhile, some variables had no correlation with advanced pentavalent immunization status such as mother’s education (p-value 0,384), affordability to health services (p-value 0,344) and the role of health workers (p-value 0,571). The conclusion is mother’s knowledge, mother’s attitude, and mother’s job status are correlated to advanced Pentavalent immunization in the working area of labuhan ratu public health Bandar Lampung city 2018.